Recovery of deformation surface of superelastic and shape memory NiTi alloy - Sneha Samal; Jan Tomáštík; Lukáš Václavek; Mohit Chandra; Jaromír Kopeček; Ivo Stachiv; Petr Šittner (Applied Surface Science Advances)
A series of indentation tests were carried out on superelastic (SE, Austenite) and shape memory alloy (SMA, Martensite) based NiTi alloys. Two types of indenters such as Berkovich and spherical indent radii of 5 and 10 µm were used in various indent loads on the surface of SE and SMA foils. Elastic and thermal surface recovery was estimated for the SE and SMA alloys at both indenters. SE sample shows the maximum recovery from deformation of 95 % at the load of 25–50 mN for the spherical indenter. However, SMA samples show a maximum recovery after heating on residual imprints of indent depth of 79 % at 250 mN load for spherical indenters. Elastic recovery in SE NiTi sample results from reverse phase transformation during unloading, however in SMA, this results from stress induced martensitic transformation. On thermal recovery SE shows recovery from shape memory region and martensite shows recovery from stress induced martensitic region. In multicycle tests, it was observed a first relative quick functional degradation of the material response, in terms of recovery capability, and a subsequent stabilization that typically occurs. Multicycle nanoindentation was performed for SE and SMA samples with a maximum load of 10 mN with a dwell time of 1s. SE shows elastic behaviour of the hysteresis curve that stabilizes after 10 cycles, however, SMA shows unrecovered strain with plasticity. On increment of the load up to 200 mN, the multicycle local indentation for SE represents the recovery of depth on each load, however overall, the unrecovered depth increases with load. However, in SMA, an increment of unrecovered depth was accumulated on each increased load.